Assessing age-related heart changes by comparing cases of sudden death during bathing and control cases in Japan. (July 2022) - Satoh, Fumiko; Irie, Wataru; Sasaki, Chizuko
Highlights: Age-related heart changes in two groups of Japanese people were compared. Of 400 sudden deaths during bathing, 136 cases (34%) had hypertension. Cardiac hypertrophy was found in 30% of the people who died suddenly during bathing. Elderly people, with or without heart disease, can die suddenly while bathing. Elderly people should not be left totally unsupervised while they bathe. Abstract: We analyzed 400 deaths that occurred in the bathtub during a 10-year period in the central area of Kanagawa prefecture in Japan. There were 72 (18%) medico-legal autopsy cases. The average age at death was 76.4 ± 11.9 years. Drowning (n = 21, 70.8%) was the most common cause of death in the 72 autopsy cases. The study examined the bodies of 40 cases within a postmortem interval of 3 days. The mean age of the 40 cases of sudden death during bathing was 68.6 ± 12.5 years. Results revealed cardiac hypertrophy in 12 cases (30%), lipofuscin deposition in 39 cases (97.5%), basophilic degeneration in 12 cases (30%), anisocytosis of the nucleus of myocardial cells in 18 cases (45%), perivascular fibrosis in 17 cases (42.5%), amyloid deposits in 1 case, and aortic valve calcification in 1 case. The hearts of control subjects who had lived to 20–99 years were also examined; the frequency of each change was higher in people older than 70 years. There was no statistically significant difference in age-related cardio-pathological changes between cases of sudden death during bathing in people in their 70s and controls in their 70s. It can be concluded that this age-related histopathological index is not related to sudden death during bathing. A large number of elderly people, including those without heart disease, have died during bathing. Preventive measures against sudden death during bathing are strongly recommended, e.g., elderly people should not be left totally unsupervised while they bathe.